THE IMPACT OF AGRICULTURAL TRADE ON FARMERS LIVELIHOOD - Ullah, Imran; Farooq, Sohail; Wadood, Fazli (The journal of contemporary issues in business and government, 2021)
Trade in agricultural commodities is an important tool in balancing the gap between the surplus and deficit regions in term of production. Being highly perishable trade of vegetables is advantageous for farmers and consumers. This study was undertaken to capture the effect of bitter gourd export on local farmers’ livelihood. Data was collected through purposive and random sampling from 120 farmers in district Charsadda of Khyber Pakhtunkhwa divided into two groups’ i.e selling their entire produce in local markets and those selling some of their produce to exporters. Simple descriptive statistics were used to analyze the data. Exporting group farmers sold almost 31 % of their produce to exporters for average price of Rs. 25/Kg as compared to price of Rs.12/Kg of local market sellers. The proportionate use of inputs and higher yield enabled the exporting farmers to cut down the unit cost to Rs. 4/Kg as compared to Rs. 5/kg of local market selling farmers. Export of vegetables benefited the farmers in three way; higher prices, better yield and lower cost.